Towards human-vehicle harmonization - Abut, Hüseyin, 1945-; Schmidt, Gerhard, Dipl.-Ing; Takeda, Kazuya, 1960-; Lambert, Jacob, active 2017-; Hansen, John H. L. (De Gruyter, 2023)
"This book features works from world-class experts from academia, industry, and national agencies focusing on a wide spectrum of automotive fields towards human-vehicle harmonization covering in-vehicle signal processing, driver modeling, systems and safety. The essays collected in this volume present cutting-edge studies on safety, driver behavior, infrastructure, and human-to-vehicle interfaces"-- Provided by publisher.
Keywords: Automobiles -- Automatic control.; Automobile driving -- Human factors.; Intelligent transportation systems.; Motor vehicles -- Electronic equipment.; elektronické knihy; electronic books